Normal Pursuit-System Limitations- First Discovered in Infantile Nystagmus Syndrome - Louis F. Dell'Osso; Jonathan B. Jacobs (Bern Open Publishing, 2013)
Infantile nystagmus syndrome (INS) patients occasionally have impaired pursuit. Model and patient data identified relative timing between target motion initiation and INS-waveform saccades as the cause. We used a new stimulus, the "step-pause-ramp" (SPR), to induce saccades proximal to target-velocity onset and test their effect on normal pursuit. Our OMS model predicted that proximal saccades impaired normal ramp responses, as in INS. Eye movements of subjects were calibrated monocularly and recorded binocularly; data were analyzed using OMtools software. Proximal saccades caused lengthened target acquisition times and steady-state position errors, confirming the model's predictions. Spontaneous pursuit oscillation supported the hypothesis that INS is caused by loss of smooth-pursuit damping. Snooth pursuit may be impaired by saccades overlapping targetmotion onset.